3D printing of ceramic microlattices and derived composites - Yap, Xiu Yun (Nanyang Technological University, 2020)
Mechanical properties of 3D printed ceramics with structural advantage were investigated. Three structures were studied namely, Kelvin Cell (bending dominated), Octet Truss (stretching dominated) and Simple Cubic lattice (stretching dominated). The structures were 3D printed using the stereolithography method at different relative densities of alumina. Across the lattices, as the relative density is increased, the compressive strength, Young’s modulus and energy absorption also increased. The ceramic lattices have higher compressive strength and stiffness, but lower strain and energy absorption compared to ductile lattices made of polymer or metal. Simple Cubic lattices have the best performance because of its vertically aligned struts that underwent mostly compressive forces. The inclined struts in Kelvin Cells and Octet Truss lattices induce higher tensile stresses in the joints, which does not work well for ceramic materials. Unlike ductile lattices, ceramic lattices undergo brittle fracture and have minimum densification phenomenon. The low relative density Kelvin Cells and Octet Truss lattices exhibit pseudoplastic behavior which would give users time to react before a catastrophic failure occurs. Another study was done on the mechanical properties of Octet Truss EpoxyAlumina Interpenetrating Phase Composite (IPC). Fabrication process for IPC was established in the study. The secondary phase provides support to the lattice and prevents catastrophic failure of Octet Truss IPC, resulting in improved specific compressive strength, strain and energy absorption. Such IPCs could potentially fill the gap for stronger structures that have higher ductility to provide better energy absorption properties per unit weight. This could be utilized in light weight shock absorption applications such as body armour and crash barriers.